Spatial analysis of contact deformation, stiffness, and flash temperature in involute gear pairs - Dong, Hongtao; Zhang, Yang; Xu, Lixin (Frontiers in Mechanical Engineering, 2025)
Gear contact behavior significantly influences system vibration, wear, and transmission efficiency. Among the factors governing this, contact deformation, flash temperature, and meshing stiffness are particularly critical. For complex tooth surfaces, especially under localized contact conditions, only partial regions engage during meshing, making the spatial distribution of mechanical and thermal parameters essential. This study presents a spatially resolved analysis of contact deformation, stiffness, and flash temperature in involute gear pairs, including spherical involute surfaces commonly found in bevel gears. By examining tangential velocity and deformation characteristics across the meshing region, the study quantifies stiffness and flash temperature distribution over the tooth surface. The interdependence of these variables is also investigated. The study’s results offer parameter-level references to support the informed selection of contact paths, especially where empirical or experience-based decisions dominate in practice. They provide theoretical support for optimizing contact path design and enhancing load capacity.